((1H-tetrazol-5-yl) methyl) pyridine-based metal coordination complexes: in situ tetrazole synthesis, crystal structures, luminescence properties1. Issue 6 (14th February 2015) - Dong, Ruoting; Chen, Xinli; Li, Qianhong; Hu, Mingyuan; Huang, Lanfen; Li, Chuwen; Shen, Moyuan; Deng, Hong
<x xml:space="preserve">Abstract</x> Six novel transition metal coordination complexes based on pyridyltetrazole ligands have been hydrothermally in situ synthesized.